(untitled) (Ius Novum, 2025)
The article is of a scientific and research-based nature. It analyses the transparency of disciplinary proceedings against academic teachers, which are conducted under the Act on Higher Education and Science. The article examines issues of transparency in light of the provisions of that Act, the Code of Criminal Procedure, and the Act on Access to Public Information. The research objective was clear: to determine whether persons not involved in disciplinary proceedings (namely the accused, their defence counsel, or the disciplinary advocate) may request access to the records of such proceedings (in whole or in part), or seek information from them other than official documents, under the Act on Access to Public Information. The analysis covered the regulations concerning the parties to disciplinary proceedings contained in the Higher Education and Science Act, the 2022 Implementing Regulation governing disciplinary procedures, and the CCP provisions applicable to disciplinary matters. The rules concerning access to public information were also analysed, both in normative terms and in light of administrative court rulings. The research employed the dogmatic method, and its findings are original and significant for both legal scholarship and practice. The study has conclusively demonstrated that information from disciplinary proceedings involving academic teachers, as well as the files of such proceedings, although considered public information, are not subject to disclosure to persons requesting access under the Act on Access to Public Information. This is because a special regulation – namely the appropriate application, under Article 305 of the Higher Education and Science Act, of Article 156(1) of that Code – excludes such applicants, until the conclusion of the disciplinary proceedings, from the group of persons who, under the current legal framework, have access to disciplinary files.